Molecular characterization of multidrug-resistant Shiga toxin-producing Escherichia coli harboring antimicrobial resistance genes obtained from a farmhouse. (18th August 2019) - Furlan, João Pedro Rueda; Gallo, Inara Fernanda Lage; de Campos, Anna Carolina Leonelli Pires; Passaglia, Jaqueline; Falcão, Juliana Pfrimer; Navarro, Armando; Nakazato, Gerson; Stehling, Eliana Guedes
ABSTRACT: Shiga toxin-producing Escherichia coli (STEC) colonize the gastrointestinal tract of animals; however, STEC may also cause severe diarrheal diseases. Food-producing animals have been acting as reservoirs and disseminators of multidrug-resistant (MDR) bacteria and antimicrobial resistance genes (ARGs); however, there are few studies characterizing molecularly bacterial isolates from sheep. Therefore, this study aimed to characterize E. coli isolates obtained from feces of sheep in a Brazilian farmhouse. A total of 14 MDR E. coli isolates were obtained from 100 feces samples, six of which were classified as non-O157 STEC ( stx1, stx2 and ehxA ). MDR E. coli isolates presented different ARGs [ bla CTX-M-Gp9, bla CMY, bla SHV, qnrS, oqxB, aac(6ʹ)-Ib, tet (A), tet (B), tet (C), sul1, sul2, and cmlA ] and plasmids (IncI1, IncFrepB, IncFIB, IncFIA, IncHI1, IncK, and ColE- like ). In addition, mutations in the quinolone-resistance determining region of GyrA (Ser83Leu; Asp87Asn) and ParC (Glu84Asp) were detected. PFGE showed a high genetic diversity (30.9 to 83.9%) and thirteen STs were detected (ST25, ST48, ST155, ST162, ST642, ST1247, ST1518, ST1725, ST2107, ST2522, ST3270, ST5036, and ST7100). Subtyping of the fimH gene showed seven fimH-type (25, 32, 38, 41, 54, 61, and 366). The results found in the present study showed high genetic diversity among MDR ARGs-producing E. coli obtained from a farmhouse. This study reports for the first time, the presence of MDR STEC and non-STEC belonging to ST25, ST162, ST642, ST1247, ST1518, ST1725, ST2107, ST3270, ST5036, and ST7100 in sheep, and contributes to the surveillance studies associated with One Health concept.